2013
DOI: 10.1073/pnas.1320302111
|View full text |Cite
|
Sign up to set email alerts
|

RNF168 ubiquitylates 53BP1 and controls its response to DNA double-strand breaks

Abstract: Defective signaling or repair of DNA double-strand breaks has been associated with developmental defects and human diseases. The E3 ligase RING finger 168 (RNF168), mutated in the human radiosensitivity, immunodeficiency, dysmorphic features, and learning difficulties syndrome, was shown to ubiquitylate H2A-type histones, and this ubiquitylation was proposed to facilitate the recruitment of p53-binding protein 1 (53BP1) to the sites of DNA double-strand breaks. In contrast to more upstream proteins signaling D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 48 publications
3
85
0
1
Order By: Relevance
“…S7B). Interestingly, a study showed that RNF168, but not RNF8, interacts with 53BP1 before their relocalization at DSB and RNF168 catalyzes Lys63-linked ubiquitylation of 53BP1, which is required for the initial recruitment of 53BP1 to DSB sites (34). Our data showing that RNF168 and 53BP1, but not RNF8 or BRCA1, were normally enriched at DSBs following INT6 silencing are in agreement with this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7B). Interestingly, a study showed that RNF168, but not RNF8, interacts with 53BP1 before their relocalization at DSB and RNF168 catalyzes Lys63-linked ubiquitylation of 53BP1, which is required for the initial recruitment of 53BP1 to DSB sites (34). Our data showing that RNF168 and 53BP1, but not RNF8 or BRCA1, were normally enriched at DSBs following INT6 silencing are in agreement with this work.…”
Section: Resultsmentioning
confidence: 99%
“…Insights provided by previous studies may help in solving this apparent paradox. Bohgaki et al (2013) showed that RNF168 interacts with 53BP1 before their assembly at DSB and RNF168 catalyzes Lys63-linked ubiquitylation of 53BP1 required for the initial localization of 53BP1 at damage sites (34). Additionally, Thorslund et al (2015) reported that overexpression of RNF168 is sufficient to restore 53BP1 recruitment at DSBs in cells that can no longer synthesize Lys63-linked ubiquitin chains (6).…”
Section: Discussionmentioning
confidence: 99%
“…52), support the importance of HR in the repair of etoposide-induced DSBs. Interestingly, in contrast to BRCA1, RNF168 deficiency only mildly affects HR-mediated DSB repair36. Therefore, the difference in the requirement for BRCA1 and RNF168 for HR-mediated repair could also contribute to the different response of BRCA1 and RNF168 deficient cells to TOP2 catalytic inhibitors and poisons.…”
Section: Discussionmentioning
confidence: 99%
“…One candidate to be investigated is 53BP1, because it has been recently demonstrated to be targeted by RNF168's activity (Bohgaki et al, 2013). Another interesting candidate is the polycomb protein Ring1b.…”
Section: Targets and Readers Of K27-linked Ubiquitin Mark On Chromatinmentioning
confidence: 99%